2011
DOI: 10.1088/0004-637x/742/2/76
|View full text |Cite
|
Sign up to set email alerts
|

Forming Realistic Late-Type Spirals in a Λcdm Universe: The Eris Simulation

Abstract: Simulations of the formation of late-type spiral galaxies in a cold dark matter (ΛCDM) universe have traditionally failed to yield realistic candidates. Here we report a new cosmological N-body/smooth particle hydrodynamic simulation of extreme dynamic range in which a close analog of a Milky Way disk galaxy arises naturally. Named "Eris," the simulation follows the assembly of a galaxy halo of mass M vir = 7.9 × 10 11 M with a total of N = 18.6 million particles (gas + dark matter + stars) within the final vi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

44
640
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 511 publications
(685 citation statements)
references
References 89 publications
44
640
1
Order By: Relevance
“…They showed that baryonic processes can suppress the abundance of small subhaloes, while simultaneously increasing the abundance of massive subhaloes compared to DM-only runs. Similar results have also been found with AREPO-simulated Milky Way zooms (Zhu et al 2016) and the Eris Simulation (Guedes et al 2011, Annalisa Pillepich, private communication) Previously, Weinberg et al (2008) had also noted the enhanced survival of subhaloes in hydrodynamical simulations, although they did not observe any suppression in halo occupation, most likely due to their low-mass resolution (mDM = 7.9 × 10 8 M ). Macciò et al (2006) had also found from a resimulation of a MW-mass halo that the number density of substructure is enhanced up to an order of magnitude in the inner regions of the halo.…”
Section: Introductionsupporting
confidence: 79%
“…They showed that baryonic processes can suppress the abundance of small subhaloes, while simultaneously increasing the abundance of massive subhaloes compared to DM-only runs. Similar results have also been found with AREPO-simulated Milky Way zooms (Zhu et al 2016) and the Eris Simulation (Guedes et al 2011, Annalisa Pillepich, private communication) Previously, Weinberg et al (2008) had also noted the enhanced survival of subhaloes in hydrodynamical simulations, although they did not observe any suppression in halo occupation, most likely due to their low-mass resolution (mDM = 7.9 × 10 8 M ). Macciò et al (2006) had also found from a resimulation of a MW-mass halo that the number density of substructure is enhanced up to an order of magnitude in the inner regions of the halo.…”
Section: Introductionsupporting
confidence: 79%
“…The above results show that in addition to the bar only model, B15, the barred-spiral N -body simulation, K14, is able to reproduce the observed peculiar LOS power spectrum very well, in contrast to the cosmological N -body simulation (Guedes et al 2011) investigated by Bovy et al (2015). This suggests that the observed peculiar motions can be explained by either a combination of a bar and transient, co-rotating spiral arms (Grand et al 2012b;Kawata et al 2014) or the bar component only as found by (Bovy et al 2015, B15).…”
Section: Resultsmentioning
confidence: 85%
“…Vela07 is one case of a disc-dominated galaxy, but even in this case, the spheroidal component has a classical, de-Vaucouleurs-like profile, n = 4.8 ± 1.1. Therefore, simulations with strong feedback have smaller spheroids (Guedes et al 2011), but their structural properties at high-z are similar to the weak-feedback runs.…”
Section: Classical Spheroids and Exponential Discsmentioning
confidence: 77%